2017
DOI: 10.1093/femsle/fnx061
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a gene encoding a membrane protein that affects exopolysaccharide production and intracellular Mg2+ concentrations in Ensifer meliloti

Abstract: Exopolysaccharides play an important role in the physiology of a bacterial cell. Ensifer meliloti is capable of producing at least two types of exopolysaccharides (EPS): succinoglycan and galactoglucan. In E. meliloti, EPS are best known for their role in mediating interaction with its symbiotic hosts. It was previously shown that high concentrations of Mg2+ or K+ were capable of suppressing the mucoid phenotype associated with galactoglucan production in an expR+ derivative of Rm1021. In an attempt to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Mutant SMc00722-38 has its insertion in mhrA. A recent study also showed DOC sensitivity when mhrA was mutated; furthermore, those mutants overproduced EPS-I, made more biofilm than the wild type, and were defective in maintaining intracellular Mg 2ϩ levels, suggesting that MhrA plays a role in magnesium homeostasis (61).…”
Section: Resultsmentioning
confidence: 99%
“…Mutant SMc00722-38 has its insertion in mhrA. A recent study also showed DOC sensitivity when mhrA was mutated; furthermore, those mutants overproduced EPS-I, made more biofilm than the wild type, and were defective in maintaining intracellular Mg 2ϩ levels, suggesting that MhrA plays a role in magnesium homeostasis (61).…”
Section: Resultsmentioning
confidence: 99%
“…ion or deoxycholate. Magnesium homeostasis related mhrA are tentatively behind this action [8]. Apart from this, exoR produces a negative biosynthesis regulator too, genetically attached with ChvG/ChvI system.…”
Section: Succinoglycan Biosynthesis Pathway and Its Role In Symbiosismentioning
confidence: 98%
“…Later, the name is changed to succinoglycan as one galactose residue per seven glucose residues are also present in the structure along with some non-carbohydrate substituents, namely pyruvate, succinate and acetate [2,3]. So far yield of bacterial succinoglycan up to 13.7 g/l [4] has only been reported from soil inhabiting bacteria like Agrobacterium tumefaciens, Agrobacterium radiobacter, Agrobacterium rhizogenes [5], Rhizobium radiobacter [6], Sinorhizobium meliloti [7], Ensifer meliloti [8] and Pseudomonas sp. [9].…”
Section: Introductionmentioning
confidence: 99%
“…Succinoglycan is a bacterial extracellular polysaccharide secreted by some soil microbes. Succinoglycan from different sources has a standard structural unit, consisting of one galactose (Gal) and seven glucose (Glc) residues, and the pyruvate group is attached to the terminal glucose residue of the side chain . Some of the succinoglycan also contains non-carbohydrate substitutions of acetate on the backbone and succinate on the branch. , However, the molecular weight and the nature of the substitution of succinoglycan may vary from source to source .…”
Section: Introductionmentioning
confidence: 99%